The role of intramural combat martial arts in enhancing well-being among international students: a combined theoretical approach - Oh, Young-Taek; Ryu, Min-Ah; Uhm, Jun-Phil (Frontiers in Psychiatry, 2025)
IntroductionInternational students often face significant psychological challenges as they navigate new cultural, academic, and social environments. Drawing on Self-Determination Theory and the Broaden-and-Build Theory, this study aimed to examine how engagement in combat martial arts enhances well-being among international students through the sequential processes of positive emotions, stress relief, and ego-resilience.MethodA total of 311 international college students who had participated in intramural combat martial arts activities were recruited through an online survey platform. Serial mediation modeling was conducted to evaluate the hypothesized model using SPSS PROCESS.ResultsOur results indicate that while engagement in combat martial arts positively influences well-being, its direct effect on ego-resilience was not significant. Positive emotions and stress relief independently mediated the relationship between physical activity engagement and well-being. The findings revealed a sequential mediation effect, where positive emotions, stress relief, and ego-resilience collectively mediated the relationshipbetween physical activity engagement and well-being.DiscussionThis study contributes to the existing literature by providing insights into the psychological mechanisms underlying international students’ well-being, and offers important practical implications for promoting mental health and resilience among this population.